The sugar disease : diabetes - Silverstein, Alvin; Silverstein, Virginia B. (New York : Lippincott, 1980)
Discusses the symptoms of diabetes, its history, causes, diagnosis, treatment, and implications for the future of current research.
Includes index.
Keywords: Diabetes -- Juvenile literature; Diabetes